Space and population - competitiveness determinants in the age of globalization = Przestrzeń i populacja - czynniki determinujące konkurencyjność w dobie globalizacji - Ostrouch, Tymon; Sługocki, Waldemar (Zielona Góra: Faculty of Economics and Management Press)
In the 21st century in a globalized world the level of competitiveness depends on numerous factors. This article concentrates deliberations on several of them, including space, population and international exchange. For ages, the international position of a country depended on its geographical size or access to sea. The country's size was also determined by its internal demographic potential.
Keywords: konkurencyjność; przestrzeń; populacja; polityka regionalna; wymiana międzynarodowa; competitiveness; space; population; regional policy; international exchange